2018
DOI: 10.1017/s0007114518000557
|View full text |Cite
|
Sign up to set email alerts
|

Eating frequency is inversely associated with BMI, waist circumference and the proportion of body fat in Korean adults when diet quality is high, but not when it is low: analysis of the Fourth Korea National Health and Nutrition Examination Survey (KNHANES IV)

Abstract: The role of eating frequency (EF) in obesity development has been debated, and few studies have investigated Asian populations. Diet quality might affect the association between EF and obesity. Therefore, we investigated the association between EF and obesity indicators in a representative sample of Korean adults with consideration to diet quality. This cross-sectional study used data of 6951 participants aged 19-93 years (male 49·8 %, female 50·2 %) from the Fourth Korean National Health and Nutrition Examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…In the present study, we observed a negative association between the anthropometric parameters and daily EF, especially before the first cycle of CT. Results from previous studies with other populations also suggest that EF may be associated with nutritional status (18)(19)(20) . A recent meta-analysis found that EF was positively associated with reductions in percentage of fat mass, as well as increases in fat-free mass.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…In the present study, we observed a negative association between the anthropometric parameters and daily EF, especially before the first cycle of CT. Results from previous studies with other populations also suggest that EF may be associated with nutritional status (18)(19)(20) . A recent meta-analysis found that EF was positively associated with reductions in percentage of fat mass, as well as increases in fat-free mass.…”
Section: Discussionmentioning
confidence: 66%
“…In addition, when establishing EF groups in the present study, women who reported ≥ 4•67 daily eating episodes had lower anthropometric values before the first cycle and after the intermediate cycle of CT. Similarly, Kim et al (18) found that Korean adults with an EF ≥ 5 daily eating episodes compared with <3 episodes had a lower BMI, WC and body fat percentage. However, the literature still presents contradictory results for the ideal number of daily eating episodes and their benefits in nutritional status (22)(23) , providing evidence for the necessity for further studies relating to these variables.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Epidemiological evidence on the association between total eating frequency (i.e. sum of meal frequency and snack frequency) and overall diet quality does not represent a consistent picture (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) . These studies should be cautiously interpreted in terms of substantial methodological problems.…”
mentioning
confidence: 99%
“…These studies should be cautiously interpreted in terms of substantial methodological problems. First, while the assessment of total eating frequency has often relied on a series of non-validated, self-report questions (1)(2)(3)(4)(5)(6) , only a few studies (9)(10)(11)(12)(13)(14) have used comprehensive information on actual dietary habits (using 24-hour dietary recall or dietary record) over multiple days to take into account the relatively large day-to-day variation at the individual level (15) . Second, there is no consensus about what constitutes a snack, a meal or an eating occasion, making it complicated to interpret the literature on this topic.…”
mentioning
confidence: 99%